(untitled) (Journal of Engineering, 2011)
This paper is a study of the effect of natural saliva (oral cavity) and a fluoride mouthwash on dental amalgams .Two types electrodes were made the first was of a high copper amalgam while the second was made from a low copper amalgam. They were immersed in two types of electrolytes for twelve hours and the whole galvanic cell was connected to a computer via a potentiosat. Their corrosion currents, corrosion voltage and corrosion resistance was recorded and compared to find which medium that is usually has the most severe effect on the amalgams corrosion.